2016
DOI: 10.1038/onc.2016.461
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation initiates multiple forms of K-Ras-independent mouse pancreatic cancer in the absence of TP53

Abstract: Chronic inflammation (CI) is a risk factor for pancreatic cancer (PC) including the most common type, ductal adenocarcinoma (PDAC), but its role and the mechanisms involved are unclear. To investigate the role of CI in PC, we generated genetic mouse models with pancreatic specific CI in the presence or absence of TP53. Mice were engineered to express either cyclooxygenase-2 (COX-2) or IκB kinase-2 (IKK2), and TP53+/+ or TP53f/f specifically in adult pancreatic acinar cells by using a full-length pancreatic ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 37 publications
(40 reference statements)
0
32
0
Order By: Relevance
“…Specifically, we envisage that KRAS mutations increase the intensity and duration of the growth-promoting signaling network. The model can accommodate multiple experimental results, including the induction of PDAC in KC mice by mutations in other genes such as the recent findings showing that chronic inflammation in mice lacking p53 develop (inefficiently) PDAC with hyperactive YAP but without KRAS mutations [261]. As YAP plays a critical role in the network, we conclude that the rationale for targeting the network (at different points) is therefore compelling.…”
Section: Discussionmentioning
confidence: 82%
“…Specifically, we envisage that KRAS mutations increase the intensity and duration of the growth-promoting signaling network. The model can accommodate multiple experimental results, including the induction of PDAC in KC mice by mutations in other genes such as the recent findings showing that chronic inflammation in mice lacking p53 develop (inefficiently) PDAC with hyperactive YAP but without KRAS mutations [261]. As YAP plays a critical role in the network, we conclude that the rationale for targeting the network (at different points) is therefore compelling.…”
Section: Discussionmentioning
confidence: 82%
“…Chronic inflammation has been shown to initiate pancreatic carcinogenesis without a K-ras mutation and in the absence of a tumor protein 53 (p53) mutation [167].…”
Section: Disruption Of Gut Bacteria Composition As Internal Pathogenimentioning
confidence: 99%
“…Studies in nongestational tissues have reported the K-Ras and H-Ras isoforms to regulate inflammation [ 42 , 43 ]. In contrast, there is limited information on the role of N-Ras and inflammation.…”
Section: Resultsmentioning
confidence: 99%